Implications of spirituality in modern living organizations. - Jiménez Rodríguez, Luis Alfredo; Gamboa Suarez, Ramiro; Vargas Ortegon, Rene (Universidad Francisco de Paula Santander, 2015)
Studies reveal that what employees want most in their jobs is a feeling of love and care and some connection between their work and their greater purpose in life. As individuals question the meaning of life and embrace the development of their inner selves, so do corporations and organizations. They perceive that their employees are collectively enjoying high morale at work; individually they are happier; they find greater motivation and personal reward in their work; and they are more effective and productive. Therefore, the purpose of the study was to investigate how entrepreneurs and senior executives define the role of spirituality in business management, how they apply it in their daily work, and what are the factors that give meaning and purpose to their work.